Hesperidin facilitating gastrointestinal motility by “Gut-brain axis” and “SCF/C-Kit signaling pathways” - Yunfei Li; Xinying Zhou; Yusong Du; Mingyuan An; Shasha Wan; Zewei Sun; Qingzhen Zhong (Poultry Science)
ABSTRACT: Hesperidin shows promising results as a potential feed additive for enhancing gastrointestinal motility in animals. Gastrointestinal function plays a pivotal role in animal growth and the digestibility of dietary nutrients, with gastrointestinal motor function serving as a crucial component. However, limited research has been conducted on the application of hesperidin as a feed additive to promote gastrointestinal motility. The present study aims to assess the efficacy of Hesperidin as a feed additive in promoting gastrointestinal motility and elucidating its underlying mechanism. A total of 200 newly hatched (1-day-old) broilers with similar body weight were randomly allocated into 4 groups as follows: the control group receiving only the basal diet, and the other 3 groups supplemented with 50, 100, and 150 mg of hesperidin per kg of the basal diet, respectively. Each group consisted of 5 replicates with ten broilers per replicate, and the feeding trial lasted for a duration of 21 d. At 21 d of age, a 5% w/v Evans Blue solution in distilled water was utilized to measure intestinal transit rates (ITR). Gastric emptying (GE) was evaluated by administering a phenol red solution at a concentration of 0.05% w/v (1 mL/broiler). Fifteen broilers from each group were euthanized and immediately dissected to obtain gizzard, hypothalamus, duodenum, and jugular blood samples. Jugular blood samples were collected for brain-gut peptide content analysis, while gizzard, hypothalamus, and duodenum samples were used for immunohistochemical analysis. Real-time qPCR was performed on gizzard samples. The results demonstrated a significant improvement in the GE and ITR of broilers in all treatment groups compared to the control group (P < 0.05), particularly in the 100mg/Kg and 150mg/Kg hesperidin group. Incorporation of hesperidin into the broilers' diet significantly enhances serum levels of ghrelin, encompassing serotonin (5-HT), motilin (MTL), cholecystokinin (CCK), and Stem Cell Factor (SCF) as well as substance P (SP) in the gizzard and duodenal tissues while reducing vasoactive intestinal peptide (VIP) levels (P < 0.05). The group administered a dosage of 150mg/Kg exhibited the most pronounced effect.Immunohistochemistry analysis revealed that hesperidin supplementation up-regulated SP protein content and down-regulated VIP protein content in the hypothalamus, gizzard, and duodenum of broilers (P < 0.05), with the most pronounced effect illustrated in the 150mg/Kg hesperidin group. Furthermore, addition of hesperidin to broiler feed resulted in a significant up-regulation of protein expression and gene expression related to SCF and The protein expression of Receptor tyrosine kinase (C-Kit) was significantly upregulated in the 150mg/Kg group, while the gene expression of C-Kit was significantly upregulated in the 50 mg/Kg group (P < 0.05). In conclusion, hesperidin exhibits promising potential as a feed additive for broilers, as its dietary supplementation of hesperidin improves gastrointestinal motility through modulation of both “gut-brain axis” signaling pathways and “SCF/C-Kit signaling pathways” within broiler chicken's digestive system. Notably, basal diet supplemented with 150mg/Kg hesperidin demonstrates superior efficacy.